Kontribusi Kreativitas Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di Kelas XI IPA MAN 2 Bukittinggi - Mega Mulyanti; Efriyanti, Liza; Musril , Hari Antoni; Okra, Riri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Low learning creativity can have an impact on the ineffectiveness of the implementation of learning, this can be seen in the low results in learning Informatics so it is necessary to analyze the influence of the contribution of learning creativity on student learning outcomes. To achieve good learning outcomes, students are required tohave creativity toward learning outcomes in informatics. This research was conducted to test the contribution of creativity to the learning outcomes of informatics. This type of research is quantitative research with a correlation approach. This study took a population of 119 students in class XI IPA MAN 2 Bukittinggi for the 2021/2022 academic year. Then the sampling used proportionate stratified random sampling of 25% so that 31 students were selected as samples. The data collection technique used a questionnaire for the independent variable data, namely the contribution of learning creativity and value documentation for the dependent variable, namely the learning outcomes of informatics. The results of this study state that: there is acontribution of learning creativity to the learning outcomes of informatics by 13% of the calculation using the product moment correlation formula, operationally data analysis turns out that the correlation number between variable X and variable Y is positive by paying attention to the magnitude of the rxy obtained, which is 0.365. Then at a significant level of 5%, an r.table value of 0.355 was obtained. It turns out that rxy (magnitude = 0.365) is much larger than r.table (magnitude = 0.355) and the coefficient of determination is 13.20% because rxy is greater than r.table, thus the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that there is a low positive correlation between the contribution of learningcreativity to student learning outcomes.